Differences in development levels of urban gminas in the Warmińsko-Mazurskie voivodship in view of the main components of sustainable development - Pawlewicz, Katarzyna (Bulletin of Geography. Socio-economic Series, 2015)
The aim of this study was to evaluate various components of sustainable development (social, spatial-environmental, economic) in urban gminas (administrative region of the 3rd order in Poland) of the Warmińsko-Mazurskie voivodship (administrative region of the 1st order in Poland). The results were used to rank the analyzed gminas in terms of their sustainable development levels. The analysis was performed with the use of Hellwig’s composite measure of development. The results were used to determine the overall value of the composite measure, calculated as the median of composite measures for each of the three components of sustainable development. The above approach was used to rank gminas in view of their sustainable development levels. Data for the analysis was supplied by the Local Data Bank of the Central Statistical Office and the Local Government Analysis System for 2010 covering 16 gminas in the Warmińsko-Mazurskie voivodship. The results of the analysis point to variations in the value of the main components of sustainable development in the evaluated urban gminas in the Warmińsko-Mazurskie voivodship.